(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2023)
In reviewing the novel Blood Rises (Krv se budi, 1932) penned by a 16-years old Belgrade novelist Ljubica P. Radoičić, the author of the paper examines its plot, time, and circumstances of its creation, and analytically points to Miss Radoičić’s sources of inspiration in the then current novelistic world literature. The author points to the influence of the main characters from the filmed novel The Sheik, 1919, by the British author Edith Hull (1880–1947), and some other translated works dealing with the life of French legionnaires in Algeria, serialised in the dailies of the time. In personal contact with the novelist, the author of the paper wrote Miss Radoičić’s first biography, also presented in this paper.